Indian floriculture: Current issues and initiatives – A review paper - KUMAR, ANSHUL; PATHANIA, SABHYA; KASHYAP, BHARATI; DHIMAN, S.R.; GUPTA, Y.C. (Journal of Ornamental Horticulture, 2024)
In India, floriculture has its roots in traditional farming, but in recent years, it has come to be recognized as having enormous potential to increase income, employ farmers, and promote economic growth. It’s quite evident that floriculture is thriving in India, and it shouldn’t be a shock considering the country’s rich history with flowers and their various uses. The favorable climate, soil quality, and abundant natural resources, coupled with cost-effective labor, make India an ideal hub for the flourishing floral industry. The world of floriculture is expanding rapidly, and it’s a pretty intense scene with constant innovation in cultivating methods and the introduction of new flower varieties. This brings about a wave of fresh products and technologies, but it also means grappling with challenges in production, marketing, and export. It’s a dynamic and competitive field that keeps evolving. In terms of infrastructure, production, marketing, and export, the Indian floriculture industry is confronted with several difficulties. Indian floriculture’s market share in the global floriculture trade will rise after adopting the proper technique. Recently, NHM was introduced as a centrally sponsored program, joining NHB, APEDA, and NABARD in supporting roles to uplift the floriculture sector in India.